2012
DOI: 10.1002/anie.201203463
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Function CXCR4 Antagonist Polyplexes To Deliver Gene Therapy and Inhibit Cancer Cell Invasion

Abstract: A bicyclam-based biodegradable polycation with CXCR4 antagonistic activity was developed with potential for combined drug/gene cancer therapies. The dual-function polycation prevents cancer cell invasion by inhibiting CXCL12 stimulated CXCR4 activation, while at the same time efficiently and safely delivers plasmid DNA into cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…We have recently reported synthesis of bioreducible poly(amido amine)s using commercial bicyclam CXCR4 antagonist Plerixafor as the main building block of the polymers (29). The synthesized polymers exhibited effective CXCR4 antagonism and demonstrated the ability to prevent invasion of cancer cells in vitro and metastasis in vivo (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported synthesis of bioreducible poly(amido amine)s using commercial bicyclam CXCR4 antagonist Plerixafor as the main building block of the polymers (29). The synthesized polymers exhibited effective CXCR4 antagonism and demonstrated the ability to prevent invasion of cancer cells in vitro and metastasis in vivo (30).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that bioreducible PAMD and PAMD/DNA polyplexes effectively inhibit cancer cell invasion mediated by SDF-1 (29). Using a Boyden chamber method, here we investigated how PEGylation affects the ability of PAMD polyplexes to inhibit invasion of cancer cells (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a competitive binding experiment, we have shown that saturating CXCR4 receptors by preincubation with a small molecule inhibitor had no effect on cell uptake or transfection activity of the DNA polyplexes. 27, 28 However, because cholesterol modification may alter the mechanism of interaction of polyplexes with cell membranes and membrane-bound receptors, it was essential to determine if the CXCR4 trafficking was involved and if any significant amount of siRNA polyplexes was trapped at the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The PAMD polymers showed dual functionality as efficient nucleic acid (gene and siRNA) delivery vectors and CXCR4 antagonists that inhibited invasion of cancer cells in vitro and decreased metastasis in several tumor models in vivo (Li et al 2012; Li and Oupicky 2014). Modification of PAMD with PEG was used to improve the in vivo applicability (Wang et al 2014).…”
Section: Inhibition Of Cxcr4 In Anticancer Therapiesmentioning
confidence: 99%